Happiness of plastic surgeons in São Paulo, Brazil: A cross-sectional study of the Brazilian Plastic Surgery Society - SBCP-SP - Marcio Yuri Ferreira; Juan Carlos Montano Pedroso; Murched Omar Taha; Lydia Masako Ferreira (Revista Brasileira de Cirurgia Plástica)
Introduction: The career of the surgeon is challenging, and scientific research has identified a prevalence of burnout in approximately 1/3 of plastic surgeons. The data on well-being and factors associated with greater happiness available specifically to plastic surgery are inconsistent and limited. The objective is to evaluate the happiness of plastic surgeons in São Paulo and which factors are associated with greater happiness. Method: This was a primary, observational, descriptive, and cross-sectional study. An online survey was conducted using a validated instrument, the Subjective Happiness Scale (SHS), which was sent to members of the Brazilian Society of Plastic Surgery-São Paulo (SBCP-SP) from December 2020 to July 2021. Sociodemographic and occupational characteristics were related to the degree of happiness measured. Results: The response rate was 12.18%, n = 268, with 70.1% males and 29.9% females. The score obtained using the SHS was 5.51 ± 0.13, and the mean score for males was 5.49 and for females was 5.57. A total of 143 (53.36%) of the participants were associate members, and 125 (46.64%) were full members of the SBCP. A total of 177 (66.04%) stated that if they could go back in time, they would choose plastic surgery again as a specialty, 62 (23.13%) perhaps, and 27 (10.82%) said that they would not. Conclusion: Plastic surgery in the state of São Paulo, Brazil, allows professionals in the specialty to have a career with high levels of happiness, including for females.